2017
DOI: 10.1186/s12888-017-1512-y
|View full text |Cite
|
Sign up to set email alerts
|

Crucial factors preceding compulsory psychiatric admission: a qualitative patient-record study

Abstract: BackgroundCompulsory admissions have a strong effect on psychiatric patients and represent a deprivation of personal liberty. Although the rate of such admissions is tending to rise in several Western countries, there is little qualitative research on the mental health-care process preceding compulsory admission. The objective of the study was to identify crucial factors in the mental health-care process preceding compulsory admission of adult psychiatric patients.MethodsThis retrospective, qualitative multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Discussions with a representative group of decision-makers found a wide range of factors that fell within four broad themes. Similar to previous findings (6,10,11,20), the clinical/risk factor theme encompasses issues that would be expected to influence decision-making (e.g., the clinical history, associated risks and the viability of alternatives to admission). This study demonstrated that clinician decision-making was influenced by wider factors that are rarely explicitly examined in studies of psychiatric admissions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Discussions with a representative group of decision-makers found a wide range of factors that fell within four broad themes. Similar to previous findings (6,10,11,20), the clinical/risk factor theme encompasses issues that would be expected to influence decision-making (e.g., the clinical history, associated risks and the viability of alternatives to admission). This study demonstrated that clinician decision-making was influenced by wider factors that are rarely explicitly examined in studies of psychiatric admissions.…”
Section: Discussionmentioning
confidence: 67%
“…The limited literature that exists identifies crisis stabilisation, potential for harm and mental state acuity as key reasons for emergency admission [e.g., (7)(8)(9)(10)(11)]. The ways these decisions are made in practise are not well-understood and clinical experience points to significant variability.…”
Section: Introductionmentioning
confidence: 99%
“…Once back in FACT Plus, they could then be monitored more closely. It is also possible that this closer contact resulted in fewer – zero versus nine – compulsory admissions, a subcategory of admissions which indicates high illness severity and low treatment adherence [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary hospitalization is now seen as the way to achieve the highest attainable standard of health when a severe exacerbation of illness impairs decision-making capacity [ 3 ], and can be lifesaving [ 4 ]. However, it represents a deprivation of personal liberty and a suspension of legal capacity [ 5 ], and conflicts with the right to personal autonomy and to make decisions about one’s own treatment [ 6 ]. Existing observational studies suggest that involuntarily admitted patients show limited clinical and social improvement [ 7 11 ], with mixed evidence on the impact on suicidality [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%